JUSTIFICATION OF RATIONAL KINEMATIC CHARACTERISTICS OF MOLDING VIBRATING TABLE - P. G. Anofriev (Nauka ta progres transportu, 2016)
Purpose. One of the efficient ways to obtain castings of complex shape is lost foam casting (LFC) in the evacuated molds (containers). Upgrading the quality of this casting method requires improvement of molding techniques. The molding process involves layer-by-layer vibratory compaction of sand in the containers. Most of the lines of LFC sections are equipped with vibrating tables with inertia oscillators driven by induction motors, operating at nominal speed. A promising way of improving the molding technique is the rational setting of the following parameters of vibrating table: vibration displacement, velocity and acceleration. These parameters are determined by the elastic-mass characteristics of the system «vibrating table – mold» and perturbing forces created by inertia oscillators. The aim of the study is to determine the rational range of setting the parameters of oscillators at which the qualitative layer-by-layer compaction of the molding sand in the mold takes place. Methodology. The efficiency criterion for setting characteristics of the vibrating table there were taken the values of averaged accelerations of 6.5 – 7.5 m/s2 corresponding to maximum compaction degree of dry molding sand and the range of acceleration values 9 – 9.5 m/s2 for giving the sand «pseudo-yielding». For the study it was developed a mathematical model of oscillations of the movable part of vibrating table with two types of casting containers for steady and transient operation modes. Findings. In the process of research of the mold oscillations it was calculated the natural frequencies of oscillations at different elastic-mass characteristics of the system using a mathematical model. It was constructed the frequency response of displacements and accelerations of the moving part of the table with container filled with molding sand layer-by-layer. Originality. The author proposes a method of determining the range of frequency setting of inertial oscillators of table, which make it possible to obtain qualitative compaction of dry molding sand in the mold. Practical value. In the process of molding using the lost foam casting models the mold mass is increasing due to the layer-by-layer filling of the mold with molding sand. The change of mass characteristics of the mold requires operational change of the kinematic characteristics of the vibrating table – vibration acceleration. The proposed mathematical model allows determining the ranges of setting the frequency parameters of inertial oscillators of molding table at all stages of molding.